2018
DOI: 10.1002/ppsc.201800346
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Boron Nitride Quantum Dots: A New 0D Material for Energy Conversion and Detection of Cellular Metabolism

Abstract: Quantum dots encompass a broad spectrum of optical, catalytic, and electrochemical properties bringing in novel applications in catalysis, imaging, displays, and optoelectronics. Herein, the unanticipated broad‐spectrum light absorption and high fluorescence quantum yield in fluorinated boron nitride (FBN) quantum dots are discussed. A heterostructure of FBN quantum dots with a wide‐bandgap semiconductor, titania nanotube arrays, exhibits high photocatalytic activity as evidenced by high external quantum effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…After Ar/SF 6 plasma treatment (Fig. 4b), the peak related to h-BN was noticed to completely disappear with the appearance of two new peaks, the first one at binding energy of 191.4 eV and can be assigned to B-F bond [31,32] and a second new peak at 193.0 eV which can be assigned to [28,29]. This indicates that the surface of BNNS is completely oxidized/ fluorized after Ar/SF 6 plasma.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…After Ar/SF 6 plasma treatment (Fig. 4b), the peak related to h-BN was noticed to completely disappear with the appearance of two new peaks, the first one at binding energy of 191.4 eV and can be assigned to B-F bond [31,32] and a second new peak at 193.0 eV which can be assigned to [28,29]. This indicates that the surface of BNNS is completely oxidized/ fluorized after Ar/SF 6 plasma.…”
Section: Resultsmentioning
confidence: 87%
“…5b) formed due to presence of N-H bond [33] or amide group [29]. In addition, the peak related to B-N bond completely disappears while a peak that can be attributed to t-BN or N-F [31,32] becomes the most intense. This t-BN is already observed in HRTEM of BNNS after Ar/SF6 plasma covering the entire surface of BNNS walls.…”
Section: B-o Bond or F-b-f Bondmentioning
confidence: 99%
“…Radhakrishnan et al [58] reported the synthesis of fluorinated BNQDs (FBNQDs) by the hydrothermal fluorination of BN nanosheets using DMF and Nafion. Nafion acted as the source for highly reactive fluorine-free radicals which reacted with BN nanosheets to break it down to form FBNQDs.…”
Section: Other Methodsmentioning
confidence: 99%
“…Therefore, the extracellular pH of tumor cells is often acidic, leading to a high extracellular acidification rate (ECAR) compared to benign cells. Radhakrishnan et al [58] reported the use of the glycolytic inhibitor, 3-bromopyruvate(3-BP), to suppress ECAR. This was demonstrated by monitoring the increase in fluorescence from FBNQDs, as a method to detect the glycolytic activity in cancer cells.…”
Section: Biosensingmentioning
confidence: 99%
See 1 more Smart Citation